Improving STFBC MIMO-OFDM with ICI self-cancellation scheme using least square error estimation / Nur Farahiah Ibrahim - Ibrahim, Nur Farahiah (2013)
Channel estimation techniques for MIMO-OFDM based on comb type pilot arrangement with LSE estimator is investigated with STF diversity implementation. The frequency offset, due to the Rayleigh fading channel, Doppler shift and oscillator synchronization in OFDM impacts its performance. This is mitigated with the implementation of the presented ICI-SC techniques and different ST subcarrier mapping. STFBC in the system exploits the spatial, temporal and frequency diversity to improve performance. Estimated channel is fed into a decoder which combines the STF decoding together with the estimated channel coefficients for equalization. The performance of the system is compared by measuring the symbol error rate with a PSK-4 and PSK-8. The results show that subcarrier mapping and ICI-SC was able to increase the system performance. LSE estimator was also able to estimate the channel coefficient at only 6 dB difference with a perfectly known channel.